Insights into the taxonomic and functional characterization of agricultural crop core rhizobiomes and their potential microbial drivers - Antonio Castellano-Hinojosa (Nature Portfolio, 2021)
Abstract While our understanding of plant–microbe interactions in the rhizosphere microbiome (rhizobiome) has increased, there is still limited information on which taxa and functions drive these rhizobiome interactions. Focusing on the core rhizobiome (members common to two or more microbial assemblages) of crops may reduce the number of targets for determining these interactions, as they are expected to have greater influence on soil nutrient cycling and plant growth than the rest of the rhizobiome. Here, we examined whether the characterization of a core rhizobiome on the basis of only taxonomic or functional traits rather than the combined analysis of taxonomic and functional traits provides a different assessment of the core rhizobiome of agricultural crops. Sequences of the bacterial 16S rRNA gene from six globally important crops were analyzed using two different approaches in order to identify and characterize the taxonomic and functional core rhizobiome. For all crops examined, we found significant differences in the taxonomic and functional composition between the core rhizobiomes, and different phyla, genera, and predicted microbial functions were dominant depending on the core rhizobiome type. Network analysis indicated potentially important taxa were present in both taxonomic and functional core rhizobiomes. A subset of genera and predicted functions were exclusively or predominately present in only one type of core rhizobiome while others were detected in both core rhizobiomes. These results highlight the necessity of including both taxonomy and function when assessing the core rhizobiome, as this will enhance our understanding of the relationships between microbial taxa and soil health, plant growth, and agricultural sustainability.